Cleaning solutions for orthodontic clear aligners: a microbiological and colorimetric analysis - Paula Cristina Henriques da SILVA; Beatriz Ribeiro RIBAS; Tony Vieira FARIA; Janaína Habib JORGE; Luiz Gonzaga GANDINI JR; Ary dos SANTOS-PINTO; João Roberto GONÇALVES; Jonas BIANCHI (Dental Press Journal of Orthodontics)
ABSTRACT Objective: This in-vitro study aimed to evaluate the antibacterial efficacy and color changes induced by different chemical agents on the orthodontic aligners. Methods: The sample consisted of Invisalign® aligners materials and seven solutions were tested: sodium hypochlorite (HYP), sodium bicarbonate (BIC), neutral detergent (DET), chlorhexidine gluconate (CX), white vinegar (VIN) diluted in water (1:3), Corega Tabs® effervescent tablets (COR), and distilled water (DW, control group). The microbiological control was evaluated by analyzing cell proliferation (CFU/ml) and cell metabolism (AlamarBlue® test), and the VITA EasyShade® Advance spectrophotometer was used for color change analysis, using multiple Mann-Whitney tests. Results: All solutions significantly reduced S. mutans biofilm (CFU/mL), except for the control group. The AlamarBlue® analysis showed a significant reduction in cell viability, except for the BIC solution (p=0.183). After 7 days, HYP showed significant color variation, compared to all the other solutions, except for the control group (p=0.095). After 14 days, BIC and CX showed significantly greater color variation than the control group (p=0.007). DET showed a large difference compared to BIC and CX (p=0.007), and a statistically significant difference compared to VIN and COR (p=0.015). Conclusion: The disinfectant solutions HYP, DET, CX, VIN, and COR significantly reduced the bacterial colonies of S. mutans and cellular metabolism. In addition, HYP, BIC, CX, and COR significantly affected the material color.